2005
DOI: 10.1111/j.1572-0241.2005.41583.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Metformin versus Vitamin E or Prescriptive Diet in Nonalcoholic Fatty Liver Disease

Abstract: Metformin treatment is better than a prescriptive diet or vitamin E in the therapy of NAFLD patients receiving nutritional counseling. Limited histological data support an association between improved aminotransferases and biopsy findings, which require confirmation in a double-blind trial with appropriate statistical power based on liver histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
438
2
16

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(480 citation statements)
references
References 34 publications
17
438
2
16
Order By: Relevance
“…107,108 An open-label trial consisting of 110 patients with NASH received either metformin 2 grams/day (55 patients), vitamin E 800 IU/day (28 patients) or dietary-induced weight loss (27 patients) for 12 months. 109 Aminotransferases improved more with metformin than with vitamin E or diet alone. However, there was only a modest improvement in hepatic steatosis and inflammation in the subset of 17 patients undergoing paired liver biopsies with metformin treatment.…”
Section: Metforminmentioning
confidence: 99%
“…107,108 An open-label trial consisting of 110 patients with NASH received either metformin 2 grams/day (55 patients), vitamin E 800 IU/day (28 patients) or dietary-induced weight loss (27 patients) for 12 months. 109 Aminotransferases improved more with metformin than with vitamin E or diet alone. However, there was only a modest improvement in hepatic steatosis and inflammation in the subset of 17 patients undergoing paired liver biopsies with metformin treatment.…”
Section: Metforminmentioning
confidence: 99%
“…Human studies have documented a reduction in aminotransferases with metformin. [6][7][8][9][10][11] However, alanine aminotransferase (ALT) breakthrough was reported, 12 suggesting that there is no sustained effect. Other 1-year trials showed no overall significant reduction in ALT values.…”
Section: Efficacy Outcomes In Nashmentioning
confidence: 99%
“…Two randomized trials showed no effect 8,14 on histology and one open-label trial showed improvement only in ballooning. 13 One study described histological improvement, 7 but the comparator arm did not undergo end-of-treatment biopsy, precluding definitive conclusions. These results could be due to metformin's weak antisteatogenic effect and no increase in adiponectin.…”
Section: Efficacy Outcomes In Nashmentioning
confidence: 99%
“…Several uncontrolled studies using volunteers without diabetes showed improvement in ALT values, liver histology, or qualitative measurements of hepatic fatty infiltration (5)(6)(7)(8). The two randomized studies supporting the effectiveness of metformin in the treatment of NAFLD excluded patients with diabetes (9,10). In the only randomized trial that studied patients with type 2 diabetes, metformin was found to have a neutral effect on liver fat infiltration (11).…”
mentioning
confidence: 99%